2018
DOI: 10.1111/jcmm.13588
|View full text |Cite
|
Sign up to set email alerts
|

MICAL1 facilitates breast cancer cell proliferation via ROS‐sensitive ERK/cyclin D pathway

Abstract: Molecule interacting with CasL 1 (MICAL1) is a multidomain flavoprotein mono‐oxygenase that strongly involves in cytoskeleton dynamics and cell oxidoreduction metabolism. Recently, results from our laboratory have shown that MICAL1 modulates reactive oxygen species (ROS) production, and the latter then activates phosphatidyl inositol 3‐kinase (PI3K)/protein kinase B (Akt) signalling pathway which regulates breast cancer cell invasion. Herein, we performed this study to assess the involvement of MICAL1 in breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 30 publications
1
35
0
Order By: Relevance
“…AKT and MAPK signaling pathways have been shown to play an important role in regulating the cell cycle and can inhibit cyclin D expression, leading to G1 phase arrest [ 21 , 22 ]. Our data showed that p-AKT and p-ERK levels were significantly decreased in CD73 knockdown cells compared with control cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…AKT and MAPK signaling pathways have been shown to play an important role in regulating the cell cycle and can inhibit cyclin D expression, leading to G1 phase arrest [ 21 , 22 ]. Our data showed that p-AKT and p-ERK levels were significantly decreased in CD73 knockdown cells compared with control cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Breast cancer is a one of the most common cancers in women worldwide [ 20 , 21 ]. Although treatment for breast cancer has improved, it still represents a high disease morbisity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…These genes have important roles in different biological and molecular processes including actin-mediated cell contraction, cardiac muscle contraction, oxidoreductase activity, and demethylase activity among others [21][22][23][24]. The top downregulated genes including Ptprf (-1.01-fold), Fgf10 (-1.03-fold), Prl2c3 (-1.034), Tgfb3 (-1.04-fold), Mical1 (-1.05-fold), Ndrg2 (-1.05-fold), Ptgs1 (-1.0487-fold), Aplp1 (-1.08-fold), and Steap3 (-1.08-fold) have important roles in processes including cell proliferation, apoptosis, regulation of DNA replication, and metabolic processes among others [25][26][27]. DEG (585 total) were subjected to Gene Ontology to establish a connection with the biological processes and molecular functions that these genes contribute to (Fig 2).…”
Section: Plos Onementioning
confidence: 99%